Internationalization of Japanese Universities in the COVID-19 Era - Shimmi , Yukiko; Ota, Hiroshi; Hoshino, Akinari (International Higher Education, 2021)
Japanese universities receiving government funding for internationalization are facing challenges implementing their original plans in the wake of the pandemic. Many among them have started using ICT tools to continue international exchanges virtually. This article explores the responses, prospects, and challenges of Japanese universities selected for the two recent government grants for internationalization, the Inter-University Exchange Project (IUEP) and the Top Global University Project (TGUP).